Are hip joint imaging findings associated with symptoms and early hip osteoarthritis features in elite male Australian Football League draftees? - Heerey, J. J.; Kemp, J. L.; Rotstein, A.; Su, S.; Li, J.; Roebert, J.; Scholes, M. J.; Girdwood, M.; Mentiplay, B.; Makdissi, M.; Shawdon, A.; Crossley, K. M. (Science and Medicine in Football, 2025)
1) describe intra-articular features (prevalence and severity) and bony hip morphology (prevalence and size) in elite male Australia Football League (AFL) draftees; 2) examine the relationship between bony hip morphology (cam and pincer morphology) and intra-articular features (cartilage defects and labral tears); and 3) examine the relationship between intra-articular features, bony hip morphology, and the Copenhagen Hip and Groin Outcome Score (HAGOS). Cross-sectional study. 58 male AFL draftees underwent 3-tesla hip MRI. Alpha angle determined cam morphology and acetabular depth defined pincer morphology. For each hip, intra-articular features were scored semi-quantitatively. All players completed the HAGOS to determine hip/groin symptoms and sports function. Logistic regression determined whether bony hip morphology was associated with labral tears and cartilage defects. Mann-Whitney U tests evaluated the difference in HAGOS subscale scores between football players with and without intra-articular features and bony hip morphology. Cam and pincer morphology were evident in 20% and 19% of hips, respectively. Nearly half of hips (41%) had a labral tear, with only 14% having a cartilage defect. Greater alpha angle was associated with the presence of labral tears (OR 1.14, 95%CI 1.07 to 1.21, p < 0.001) but not cartilage defects. Hip imaging findings were not associated with lower (worse) HAGOS scores. Hip joint imaging findings were common in elite male AFL draftees but not associated with worse pain, symptoms, or sport function. Cam morphology may contribute to the development of labral tears in male AFL draftees.